Both Galactosaminogalactan and α-1,3-Glucan Contribute to Aggregation of Aspergillus oryzae Hyphae in Liquid Culture - Miyazawa, Ken; Yoshimi, Akira; Sano, Motoaki; Tabata, Fuka; Sugahara, Asumi; Kasahara, Shin; Koizumi, Ami; Yano, Shigekazu; Nakajima, Tasuku; Abe, Keietsu (Frontiers in Microbiology, 2019)
Filamentous fungi generally form aggregated hyphal pellets in liquid culture. We previously reported that α-1,3-glucan-deficient mutants of Aspergillus nidulans did not form hyphal pellets and their hyphae were fully dispersed, and we suggested that α-1,3-glucan functions in hyphal aggregation. Yet, Aspergillus oryzae α-1,3-glucan-deficient (AGΔ) mutants still form small pellets; therefore, we hypothesized that another factor responsible for forming hyphal pellets remains in these mutants. Here, we identified an extracellular matrix polysaccharide galactosaminogalactan (GAG) as such a factor. To produce a double mutant of A. oryzae (AG-GAGΔ), we disrupted the genes required for GAG biosynthesis in an AGΔ mutant. Hyphae of the double mutant were fully dispersed in liquid culture, suggesting that GAG is involved in hyphal aggregation in A. oryzae. Addition of partially purified GAG fraction to the hyphae of the AG-GAGΔ strain resulted in formation of mycelial pellets. Acetylation of the amino group in galactosamine of GAG weakened GAG aggregation, suggesting that hydrogen bond formation by this group is important for aggregation. Genome sequences suggest that α-1,3-glucan, GAG, or both are present in many filamentous fungi and thus may function in hyphal aggregation in these fungi. We also demonstrated that production of a recombinant polyesterase, CutL1, was higher in the AG-GAGΔ strain than in the wild-type and AGΔ strains. Thus, controlling hyphal aggregation factors of filamentous fungi may increase productivity in the fermentation industry.